CRESCIMENTO INFANTIL E ALEITAMENTO MATERNO EXCLUSIVO: estudo comparativo com uma referência e um padrão internacional de crescimento - Jaldin, Maria da Graça Mouchrek (2009)
The aim of the present study was to evaluate the growth of exclusively breast-fed infants from birth to six months of age, as well as to compare weight, length and head circumference with the National Center for Health Statistics (NCHS/1978) reference, and the new international World Health Organization standard/2006 (WHO/2006). A prospective longitudinal study, undertaken in the Human Milk Bank of the Child Maternal University Hospital in São Luis, Maranhão-Brazil, in the period of October 2007 to November 2008. A convenience sampling of 328 full term singleton infants, with birth weight equal to or over 2.5 kg and lower or equal to 4.0kg, exclusively breastfed, upon demand, since their birth. The weight, length and head circumference recorded from birth to the sixth month of age. The growth was evaluated through mean standard deviation and percentiles, and the results were compared to those of the NCHS/1978 reference and WHO/2006 standard. A total of 181 infants (95 females and 86 males) concluded the study. The mean weight of infants at birth was 3.3kg and 8.2kg at six months for males, and 7.7kg for females. Males weighed more than females from the first to the sixth month (p<0.05). The greatest velocity in weight gain occurred in the first two months of life for both sexes. Both males and females doubled their mean birth weight around the third and fourth months, respectively. The mean weight of females was superior to the WHO/2006 standard, at birth and from the third to the sixth month (p<0.05); as to the males, it was superior from the fourth to the sixth month (p<0.05). The mean weight was above the NCHS/1978 reference, for both genders, from birth to the sixth month (p<0.05) except for males at birth. The mean length at birth was 49.1cm (males) and 48.9cm (females), and it was 67.0 cm (males) and 65.4cm (females) at the sixth month. The mean length of males was lower than the WHO/2006, from birth to the sixth month (p<0.05), except for the fifth month; it was also lower than the NCHS/1978 at birth, in the first, fourth and sixth months of life (p<0.05). As to the females, it was similar to the WHO/2006 and lower than the NCHS/1978, at birth and at the sixth month (p<0.05). The 50th percentile of weight of infants was comparable to WHO/2006 percentile, and the females and males surpassed the standard measure from the second and third months, respectively. The 50th percentile of the infants weight was superior to the NCHS/1978 from the first to the sixth month. The 50th percentiles of length and head circumference were comparable to the respective percentiles of the standard and the reference. The infants velocity of the monthly weight increment followed the 50th percentile curve of the WHO/2006, with a better performance, however. It was concluded that exclusively breast-fed infants up to six months presented satisfactory growth. The weight, length and head circumference were akin to the 50th percentile of the WHO standard and NCHS reference; however, the infants in the study were heavier than the reference.